TRADISI NYELEH DALAM ACARA PERKAWINAN SEBAGAI AKAD TA'AWUN (STUDI KASUS DI DESA PARIT KELADI KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT) - Ervina Resyia; Syai’in Syai’in (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The nyeleh tradition is a practice of the Parit Keladi Village community in the form of giving goods at wedding ceremonies which are considered as a form of mutual assistance. However, because of the recording and the expectation of a return in a similar form, this tradition tends to be a social burden. This study aims to analyze the nyeleh tradition as a ta'awun contract and assess it from the perspective of sharia economic law. Using a juridical-empirical approach and descriptive-qualitative methods, data were collected through observation, interviews, documentation, and literature studies. The results of the study indicate that this tradition contains solidarity values, but has the potential to shift into a qardh contract if accompanied by social pressure. There is a gap between sharia principles that emphasize sincerity (das sollen) and practices that are socially reciprocal (das sein). Therefore, understanding of sharia needs to be strengthened so that this tradition remains a legitimate and fair form of mutual assistance.